Morphological effects of G-quadruplex stabilization using a small molecule in zebrafish - Agarwal, Tani; Lalwani, Mukesh Kumar; Kumar, Santosh; Roy, Saumya; Chakraborty, Tushar Kanti; Sivasubbu, Sridhar; Maiti, Souvik (Biochemistry, 2014)
Zebrafish (Danio rerio) embryos are transparent and advantageous for studying early developmental changes due to ex utero development, making them an appropriate model for studying gene expression changes as a result of molecular targeting. Zebrafish embryos were injected with a previously reported G-quadruplex selective ligand, and the phenotypic changes were recorded. We report marked discrepancies in the development of intersegmental vessels. In silico analysis determined that the putative G-quadruplex motif occur in the upstream promoter region of the Cdh5 (N-cadherin) gene. A real-time polymerase chain reaction-based investigation indicated that in zebrafish, CDH-2 (ZN-cad) was significantly downregulated in the ligand-treated embryos. Biophysical characterization of the interaction of the ligand with the G-quadruplex motif found in this promoter yielded strong binding and stabilization of the G-quadruplex with this ligand. Hence, we report for the first time the phenotypic impact of G-quadruplex targeting with a ligand in a vertebrate organism. This study has unveiled not only G-quadruplex targeting in non-human animal species but also the potential that G-quadruplexes can provide a ready tool for understanding the phenotypic effects of targeting certain important genes involved in differentiation and developmental processes in a living eukaryotic organism.